Synthetic Studies on Huperzine R: Construction of the 1-Azabicyclo[5.4.3]tetradec-6-ene Core - Kumazaki, Hiroshi; Nakajima, Rie; Bessho, Yuka; Yokoshima, Satoshi; Fukuyama, Tohru (Synlett, 2015)
Synthetic studies on huperzine R are described. The 1-azabicyclo[5.4.3]tetradec-6-ene core was constructed by elimination of an ammonium salt formed at a position β to a carbonyl group.
Keywords: alkaloids; ammonium salts; lactams; asymmetric synthesis; polycycles